To Enhance Performance of Light Soaking Process on ZnS/CuIn1-xGaxSe2 Solar Cell - Yu-Jen Hsiao; Chung-Hsin Lu; Te-Hua Fang (International Journal of Photoenergy)
The ZnS/CuInGaSe2 heterojunction solar cell fabricated on Mo coated glass is studied. The crystallinity of the CIGS absorber layer is prepared by coevaporated method and the ZnS buffer layer with a band gap of 3.21 eV. The MoS2 phase was also found in the CuInGaSe2/Mo system form HRTEM. The light soaking effect of photoactive film for 10 min results in an increase in F.F. from 55.8 to 64%, but series resistivity from 7.4 to 3.8 Ω. The efficiency of the devices improved from 8.12 to 9.50%.